Vaginal endodermal sinus tumor in an infant: a case report - Borja-Zapata, Boris (2025)
Background: Endodermal sinus tumor is a malignant germ cell neoplasm, most commonly of gonadal origin. Its occurrence in the vagina is extremely rare. Case description: We report the case of a 7-month-old infant presenting with intermittent vaginal discharge and bleeding for 3 months. Initial ultrasound revealed a vascularized hypoechoic lesion located in the upper vaginal canal. Laboratory tests showed elevated serum alpha-fetoprotein levels (range: 1,415–2,500 ng/mL). Subsequent magnetic resonance imaging identified a solid tumor in the upper third of the vaginal canal, with mass effect on adjacent structures, avid heterogeneous contrast enhancement, diffusion restriction, and no evidence of regional infiltration. Histopathological analysis of an expelled vaginal blood clot confirmed the diagnosis of endodermal sinus tumor with Schiller-Duval bodies. The patient underwent six cycles of chemotherapy with bleomycin, etoposide, and cisplatin over 6 months, without clinical complications. Follow-up imaging 3 months after completion of treatment showed a reduction in tumor size and no evidence of intra- or extrapelvic metastases. Alpha-fetoprotein levels progressively decreased. A subsequent biopsy was negative for malignant neoplasia. Conclusion: Vaginal endodermal sinus tumor represents an extremely rare extragonadal presentation, primarily observed in infancy. Imaging plays a crucial role in the diagnosis, follow-up, and therapeutic planning of this entity.